The Effects of Leptin on Glial Cells in Neurological Diseases - Fujita, Yuki; Yamashita, Toshihide (Frontiers in Neuroscience, 2019)
It is known that various endocrine modulators, including leptin and ghrelin, have neuroprotective roles in neurological diseases. Leptin is a hormone produced by adipocytes and was originally identified as a gene related to obesity in mice. The leptin receptors in the hypothalamus are the main target for the homeostatic regulation of body weight. Recent studies have demonstrated that leptin receptors are also expressed in other regions of the central nervous system (CNS), such as the hippocampus, cerebral cortex, and spinal cord. Accordingly, these studies identified the involvement of leptin in the regulation of neuronal survival and neural development. Furthermore, leptin has been shown to have neuroprotective functions in animal models of neurological diseases and demyelination. These observations also suggest that dysregulation of leptin signaling may be involved in the association between neurodegeneration and obesity. In this review, we summarize novel functions of leptin in animal models of neurodegenerative diseases. Specifically, we focus on the emerging evidence for the role of leptin in non-neuronal cells in the CNS, including astrocytes, microglia, and oligodendrocytes. Understanding leptin-mediated neuroprotective signals and molecular mechanisms underlying remyelination will be helpful to establish therapeutic strategies against neurological diseases.